Providing an Additional Electron Sink by the Introduction of Cyanobacterial Flavodiirons Enhances Growth of A. thaliana Under Various Light Intensities - Tula, Suresh; Shahinnia, Fahimeh; Melzer, Michael; Rutten, Twan; Gómez, Rodrigo; Lodeyro, Anabella F.; von Wirén, Nicolaus; Carrillo, Néstor; Hajirezaei, Mohammad R. (Frontiers in Plant Science, 2020)
The ability of plants to maintain photosynthesis in a dynamically changing environment is of central importance for their growth. As the photosynthetic machinery is a sensitive and early target of adverse environmental conditions as those typically found in the field, photosynthetic efficiency is not always optimal. Cyanobacteria, algae, mosses, liverworts and gymnosperms produce flavodiiron proteins (Flvs), a class of electron sinks not represented in angiosperms; these proteins act to mitigate the photoinhibition of photosystem I under high or fluctuating light. Here, genes specifying two cyanobacterial Flvs have been expressed in the chloroplasts of A. thaliana in an attempt to improve plant growth. Co-expression of Flv1 and Flv3 enhanced the efficiency of light utilization, boosting the plant’s capacity to accumulate biomass as the growth light intensity was raised. The Flv1/Flv3 transgenics displayed an increased production of ATP, an acceleration of carbohydrate metabolism and a more pronounced partitioning of sucrose into starch. The results suggest that Flvs are able to establish an efficient electron sink downstream of PSI, thereby ensuring efficient photosynthetic electron transport at moderate to high light intensities. The expression of Flvs thus acts to both protect photosynthesis and to control the ATP/NADPH ratio; together, their presence is beneficial for the plant’s growth potential.